2017
DOI: 10.1093/ofid/ofx163.013
|View full text |Cite
|
Sign up to set email alerts
|

Detection of (1,3)-β-d-Glucan in Cerebrospinal Fluid in Histoplasma Meningitis

Abstract: Background Central nervous system (CNS) histoplasmosis is a life-threatening condition, and represents a diagnostic and therapeutic challenge. Although CSF (1,3)-β-d-glucan (CSF BDG) is available as a biologic marker for diagnosis of fungal meningitis, there are limited data on its use for diagnosis of Histoplasma meningitis. We evaluated CSF BDG detection using the Fungitell assay in patients with CNS histoplasmosis and controls.Methods Patients were classified as cases if there was CNS inflammation (CSF WBC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…1,3-Beta-D-glucan 1,3-Beta-D-glucan (BDG) measurement in CSF has been used to detect a variety of fungi including all fungi discussed below, yet specificity for any individual fungi is inadequate [14,124,125]. Although it was previously thought that Cryptococcus did not release sufficient BDG for detection, this was disproven by Rhein and colleagues who found that among HIV-infected patients with cryptococcal meningitis, BDG showed a sensitivity of 89% and specificity of 85% compared with cryptococcal antigen detection with higher BDG levels being associated with mortality [11,125,126].…”
Section: Diagnostic Techniques For Multiple Types Fungal Meningitismentioning
confidence: 99%
See 2 more Smart Citations
“…1,3-Beta-D-glucan 1,3-Beta-D-glucan (BDG) measurement in CSF has been used to detect a variety of fungi including all fungi discussed below, yet specificity for any individual fungi is inadequate [14,124,125]. Although it was previously thought that Cryptococcus did not release sufficient BDG for detection, this was disproven by Rhein and colleagues who found that among HIV-infected patients with cryptococcal meningitis, BDG showed a sensitivity of 89% and specificity of 85% compared with cryptococcal antigen detection with higher BDG levels being associated with mortality [11,125,126].…”
Section: Diagnostic Techniques For Multiple Types Fungal Meningitismentioning
confidence: 99%
“…There remains a FDA-required black-box label incorrectly stating that Cryptococcus does not produce BDG. CSF BDG has also been studied for Histoplasma meningitis with a sensitivity of 53% and specificity of 87% [124]. Thus, while BDG may have utility in steering clinicians towards fungal meningitis -BDG is not able to reliably diagnose any particular fungal pathogen.…”
Section: Diagnostic Techniques For Multiple Types Fungal Meningitismentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies revealed that CSF (1,3)-β-D-glucan was a surrogate marker for PCM, and the persistence of (1,3)-β-D-glucan in CSF was associated with the clinical and microbiological failure of PCM (Lyons et al, 2015;Ceccarelli et al, 2016;Farrugia et al, 2016). Although elevated CSF (1,3)-β-D-glucan was not specifically present in CNS infections of Aspergillus, Cryptococcus and Histoplasma (Rhein et al, 2014;Chen et al, 2017;Myint et al, 2018), CSF (1,3)-β-D-glucan testing may still be a useful surrogate marker of C. meningitis (Davis et al, 2020). Although it seemed that a single episode of CSF Candida was insufficient for PCM diagnosis, a study indicated that normal CSF parameters were found in 43% (3/7) of infants with C. meningitis, and only 37% (7/19) of them had positive blood cultures for Candida (Cohen-Wolkowiez et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Another study assessed the role of the MVista ® IgG and IgM antibody EIA 66 and of 1,3-beta-D-glucan detection 85 in CSF for diagnosis of meningitis. Culture of CSF was positive in 19.1% (9 of 47).…”
Section: Diagnosis Of Meningitismentioning
confidence: 99%